Peran Ukuran Perusahaan Dalam Memoderasi Rasio Keuangan Terhadap Cash Holding - Cang, Jexine Thalia; Pinny, Pinny; Chaterine Vania (Owner : Riset dan Jurnal Akuntansi, 2024)
A corporation is a legal entity established to conduct economic activities aimed at generating profits or achieving a specific goal. However, due to the increasing competition and dynamism of the economy, companies are indirectly required to have accurate financial management. The objective is to determine the ideal cash supply for a business. This study aims to analyze the impact of capital expenditure, leverage, liquidity, net working capital, and profitability on the cash holding variable, with the company size as a moderator in manufacturing companies listed on the Indonesian Stock Exchange for 2021-2022. The study will employ quantitative descriptive research and use library and documentation research methods as data collection techniques. The source of data used is the financial statements of manufacturing companies listed on the Indonesian Stock Exchange for 2021-2022, which are secondary data. This study will use purposive sampling based on specific criteria to obtain 424 samples over a two-year observation period. SmartPLS software version 3.2.9 will be used to conduct the research by utilizing Partial Least Square - Structural Equation Modeling with a two-stage test approach to analyze the research data. The research will be analyzed using the outer model test and the inner model test using formative components. The findings of this study interpret that capital expenditure, leverage, and liquidity do not have a significant influence on cash holding.